Moisture Dependent Selected Postharvest Engineering Properties of Ragi (Eleusine coracana) Grown in Northern Hills of India - Goswami, D; Manikantan, M R; Gupta, R K; Vishwakarma, R K (Journal of Postharvest Technology, 2015)
The machines and systems for processing and value addition of ragi are totally dependent on its postharvest engineering properties. These properties are further, greatly affected by the moisture content of the grains. As ragi processing and value addition requires different set of moisture contents, the present study was aimed at assesment of selceted postharvest engineering properties of ragi (cv. VL Mandua -315), grown in Himalayan regions of India as a function of its moisture content (8- 40%, wb). The spatial dimensions, geometric mean diameter, thousand grain mass, angle of repose, sphericity, surface area and porosity increased with increasing moisture content of the grains. The bulk density and true density decreased linearly from 777.50 to 684.99 kg/m3 and from 1270.44 kg/m3to 1236.48 kg/m3, respectively with the moisture content. The values of static coefficient of friction of ragi against plywood, mild steel, galvanized iron and glass increased from 0.57, 0.52, 0.35 and 0.30 to 0.83, 0.72, 0.79 and 0.70, respectively. The hardness decreased with moisture (67.95 N to 37.51 N) whereas toughness first increased from 5.17 Nmm (8% moisture) to 6.91 Nmm (24% moisture) followed by decrease to 3.97 Nmm at 40% moisture content.